The relationship of adolescent knowledge about the risks of early marriage with the desire to engage in early marriage - Angraeni, Kadek Noni; Lestari, Sri (Universitas 'Aisyiyah Yogyakarta, 2023)
According to BKKBN, early marriage is a marriage that occurs before the child is 21 years old for women and before 25 years for men, at which age the health and psychological conditions are immature. Early marriage can cause health risks for mothers and babies born, psychological risks, social risks and even high rates of early marriage can negatively risk economic growth and a country's ability to alleviate poverty. The purpose of this study was to determine the relationship between adolescent knowledge about the risk of early marriage and the desire to do early marriage. This research method is quantitative correlation with cross sectional approach. The sample was taken using the purposive sampling method with a total of 137 respondents in grade X students at SMAN 1 Banguntapan Bantul. The tool in this study was a questionnaire. The data collected were analyzed univariately and bivariately. Based on the level of knowledge about the risks of early marriage, most adolescents have good knowledge as many as 132 people (96.4%) and based on the desire to do early marriage, most adolescents do not want to do early marriage as many as 135 people (98.5%). The results of the chi square analysis obtained a value of p-value = 0.001 (p-value = <0.05) with a correlation coefficient value of 0.625 or in the strong category (0.6-0.799). It was concluded that there is a relationship between adolescent knowledge about the risks of early marriage and the desire to marry early. The suggestion for midwives of Banguntapan 1 Health Center is to maintain cooperation with SMA N 1 Banguntapan Bantul in providing education to students, especially emphasized the social risks of early marriage